The Effect of Poloxamer 188 on the Solubility and Dissolution Behaviors of Piroxicam-PEG 4000 Solid Dispersions - Yugatama, Adi; Azizah, Anas Muti'ah Syahrul; Choiri, Syaiful; Huang, Ya-lin (Sciences of Pharmacy, 2025)
Piroxicam (PRX), a non-steroidal anti-inflammatory drug (NSAID), is classified as a biopharmaceutical classification system class II (high permeability and low solubility), which limits its bioavailability. Enhancement of the dissolution rate is a key strategy to enhance the absorption. Solid dispersion systems, particularly when combined with amphiphilic multiple co-block polymers, offer a promising approach to address this challenge. This study aimed to investigate the effect of Poloxamer 188 (P188) and the solid dispersion technique on the solubility and dissolution rate of PRX. Polyethylene glycol (PEG) 4000-based solid dispersions containing PRX were prepared using varying concentrations of Poloxamer 188 surfactant through the fusion method. The solid dispersions were evaluated for saturated solubility in water for 24 hours. Selected formulations were further characterized using thermal analysis and vibrational spectroscopy. The optimized solid dispersion formulation was filled into capsules, and a dissolution assay was carried out to compare its performance with that of pure PRX capsules. The optimized formula, comprising 3% P188 and PEG4000, demonstrated a significant enhancement in saturation solubility parameters (p < 0.05), specifically the Cmax/S0 ratio. Additionally, dissolution testing showed a 22.22% increase in the dissolution rate of the PRX solid dispersion capsules compared to pure PRX capsules. In conclusion, P188-based solid dispersion containing PRX enhanced the solubility and dissolution rate, potentially improving therapeutic efficacy.